2020
DOI: 10.3389/fmicb.2020.00291
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Polymicrobial Biofilm Keratinocyte Colonization Model for Exploring Interactions Between Commensals, Pathogens and Antimicrobials

Abstract: Skin offers protection against external insults, with the skin microbiota playing a crucial defensive role against pathogens that gain access when the skin barrier is breached. Linkages between skin microbes, biofilms and disease have not been well established although single-species biofilm formation by skin microbiota in vitro has been extensively studied. Consequently, the purpose of this work was to optimize and validate a simple polymicrobial biofilm keratinocyte model for investigating commensal, pathoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 59 publications
(85 reference statements)
1
24
0
Order By: Relevance
“…Polymicrobial biofilms formed by a mixture of commensal strains ( Staphylococcus epidermidis and Micrococcus luteus ) and pathogens ( Staphylococcus aureus and Pseudomonas aeruginosa ) were also used to study the interactions among commensal organisms, pathogens, and human keratinocytes. The authors observed that the commensal organisms reduced the damage caused to the keratinocyte monolayer by pathogens, reduced biofilm thickness, and formed a layer between the keratinocytes and pathogens [ 117 ] .…”
Section: Future Insightsmentioning
confidence: 99%
“…Polymicrobial biofilms formed by a mixture of commensal strains ( Staphylococcus epidermidis and Micrococcus luteus ) and pathogens ( Staphylococcus aureus and Pseudomonas aeruginosa ) were also used to study the interactions among commensal organisms, pathogens, and human keratinocytes. The authors observed that the commensal organisms reduced the damage caused to the keratinocyte monolayer by pathogens, reduced biofilm thickness, and formed a layer between the keratinocytes and pathogens [ 117 ] .…”
Section: Future Insightsmentioning
confidence: 99%
“…To test this hypothesis, human skin keratinocytes were used to evaluate the survival capacity of S. pettenkoferi SP165. HaCaT is a non-transformed human keratinocyte line that has been used to investigate epithelial infection 25 , cytotoxicity 26 , biofilm formation 27 , and skin cancer 28 . It can also be employed in models of skin wound infection where the stratum corneum is disrupted and bacteria come into close contact with living keratinocytes 27 .…”
Section: S Pettenkoferi Persists Within Murine and Human Macrophagesmentioning
confidence: 99%
“…HaCaT is a non-transformed human keratinocyte line that has been used to investigate epithelial infection 25 , cytotoxicity 26 , biofilm formation 27 , and skin cancer 28 . It can also be employed in models of skin wound infection where the stratum corneum is disrupted and bacteria come into close contact with living keratinocytes 27 . Therefore, we performed invasion experiments to address the persistence of S. pettenkoferi SP165 since S. aureus has been demonstrated to proliferate and persist intracellularly in HaCaT cells 29,30 .…”
Section: S Pettenkoferi Persists Within Murine and Human Macrophagesmentioning
confidence: 99%
“…Furthermore, using transcriptomes, several studies have shown that bacterial behavior in the laboratory is not consistent with the behavior in a natural in situ environment 38 , 39 . Aiming to more accurately replicate native environments, several new model systems have been developed, including artificial urine media 40 for an investigation into polymicrobial urinary tract infections, complex skin organoids for skin-community colonization 41 , the inclusion of food-grade fibers in a gut model 42 , as well as several systems facilitating cultivation in native environments 15 , 16 . These models, based on researcher rationale, are likely superior models, but without validation it is unclear how they compare to the native environment.…”
Section: Mimicking Nature’s Complexitymentioning
confidence: 99%